2017
DOI: 10.1088/1741-2552/aa8416
|View full text |Cite
|
Sign up to set email alerts
|

Invariance and variability in interaction error-related potentials and their consequences for classification

Abstract: The obtained results may be used to explain across-study variability of ErrPs, as well as to define guidelines for approaches to the ErrP classifier transferability problem.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 83 publications
2
16
0
Order By: Relevance
“…It has been shown in several studies that ErrPs can be decoded (see [ 9 , 10 ] for a review about decoding ErrPs) and how the performance of the decoder can be optimized using different types of features [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], classifiers [ 11 , 12 , 17 , 18 , 22 , 23 ], time windows [ 24 , 25 , 26 ], and channels [ 17 , 25 , 27 , 28 ]. Moreover, it has been shown that generalized ErrP detectors can be transferred across different tasks and types of ErrPs such as observation and interaction ErrPs, across participants, and time which eliminates the need for calibration (see, e.g., [ 11 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]). This transfer may be successful due to the stability of the ErrP over time as good test/retest reliability has been reported for evoking the ErrP [ 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…It has been shown in several studies that ErrPs can be decoded (see [ 9 , 10 ] for a review about decoding ErrPs) and how the performance of the decoder can be optimized using different types of features [ 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 ], classifiers [ 11 , 12 , 17 , 18 , 22 , 23 ], time windows [ 24 , 25 , 26 ], and channels [ 17 , 25 , 27 , 28 ]. Moreover, it has been shown that generalized ErrP detectors can be transferred across different tasks and types of ErrPs such as observation and interaction ErrPs, across participants, and time which eliminates the need for calibration (see, e.g., [ 11 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 ]). This transfer may be successful due to the stability of the ErrP over time as good test/retest reliability has been reported for evoking the ErrP [ 37 , 38 , 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, this classifier showed poor between-day and across-participant transfer [16], which suggests that calibration data for the classifier need to be collected every time it is going to be used. This can be a time-consuming process and it should be considered whether other, more generic approaches should be used [43,[49][50][51], that can be individualized/adapted [17,52] to the user while an error monitoring/correction system is in use. Alternatively, it should be considered or whether a type of ErrP should be used in which multiple trials can be obtained more rapidly, such as observational ErrPs [53], or with higher error/correct ratios [25,54].…”
Section: Discussionmentioning
confidence: 99%
“…Simple discrete and controlled tasks enable a clear distinction between correct and erroneous events [5], [7], [11], [14]. This allows for a straightforward assessment of ErrP variations from the perspective of classification and visualization of grand average waveforms.…”
Section: Experiments Design For Analysismentioning
confidence: 99%
“…Nevertheless, common ErrP variations (i.e., augmentations in the observed ErrP signal structure) have been able to be detected, likely due to the underlying invariant features for these ErrPs [11]. For instance, observation are elicited in response to observed erroneous action [5]; feedback are elicited when feedback indicates an erroneous choice or action was made [4]; outcome are elicited when the goal of an action is not achieved [6], [12]; execution or interaction 1 are elicited when an action is input to an interface and the interface outputs an erroneous action instead [5], [6], [12].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation